The effect of the gap between the cast post and residual gutta-percha and cement type on microleakage of endodontically treated teeth using the fluid filtration method - Ramin Mosharraf; Saeid Farahmand; Sarah Arzani; Hamidreza Hemati; Majid Abolhasani; Behnam Golshirazi; Sharare Jahangiri (Dental Research Journal)
Background: The aim of this study was to investigate the impact of the distance between the gutta-percha and the post, as well as the type of cement used, on the incidence of microleakage in endodontically treated teeth. Materials and Methods: This experimental-laboratory study involved 72 single-canal, single-rooted teeth, which were randomly sorted into six study groups and two control groups, each containing nine teeth. The six groups were further divided based on the distance between gutta-percha and post (0 mm, 0–2 mm, and >2 mm) and then categorized by cement type into glass ionomers and resins. Microleakage was evaluated using the fluid filtration method at 15 and 30 days. Data were analyzed using SPSS software, employing between-subjects effects and post hoc Tukey tests at a 5% significance level. Results: Cement type did not significantly affect microleakage (P = 0.598). However, microleakage increased significantly with larger gaps between the post and remaining gutta-percha (P = 0.002). No significant difference in microleakage was observed between the gapless and ≤2 mm groups (P = 0.328). Similarly, ≤2 mm and >2 mm groups did not show any notable difference (P = 0.054). However, the difference in microleakage between the gapless group and the ≥2 mm gap group was significant (P = 0.001). Conclusion: This study found no significant difference in microleakage between glass ionomers and resin cements. Only gaps >2 mm significantly affected microleakage.